Gut microbiota and Helicobacter pylori infections - Khosravi, Y.; Seow, S.W.; Teh, X.S.; Ramli, N.S.K.; Gunaletchumy, S.P.; Loke, M.F.; Bunte, R.M.; Pettersson, S.; Goh, K.L.; Vadivelu, J. (Blackwell Publishing, 2012)
Background: It has been widely accepted that Helicobacter pylori may be the only bacterium that can survive and infect the human stomach. Recently, a few studies using 16S rRNA clone library and other similar approaches showed that the gastric microbiome may be more complex than that. However, the role of interactions between H. pylori and other members of the gastric and gut microbiome in the development and progression of gastroduodenal diseases has not been extensively studied. Objective: The objective of this study is to establish the effects of gut microbiome microbiome in H. pylori infections using germ-free (GF) and specific pathogen-free (SPF) mice models. Methodology: Male GF and SPF C57BL/6 mice of 4–8 weeks of age were infected intragastrically with 109 CFU of rodent-adapted H. pylori strain 7.13 for 2, 8 and 16 weeks. At the end of the respective infection period, the animals were sacrificed. Stomach, liver and brain were harvested for microbiological and histopathological examinations. Synaptophysin and polysynaptic density protein 95 (PSD-95) levels in the brain were evaluated. Blood samples were collected for immunological and hormonal (leptin, total ghrelin and acyl ghrelin) analysis. Results: GF mouse model was established as an alternative animal model for studying H. pylori infections in a microbiota-free in vivo system. Discussion and conclusion: To further characterize the interplay between H. pylori, gut microflora and host, a meta-proteomics and meta-metabo-lomics approach will also be adopted. Outcome of this study will enhance our understanding of the pathogenesis of H. pylori-associated diseases in a systemic in vivo model against a complex multispecies environment.